Effect of Bicomat and Tithonia Compost on Bok Choi (Brassica rapa L.) Productivity in Two Soil Types - Wilujeng, Retno; Apriyanti, Kristin; Subianto, Edwin; Primadona, Primadona; Gunevo, Pilipus; Reku, Efraim Umbu; Jaspis, Yakobus; Cahya, Utik Tri Wulan; Widowati, Widowati (Jurnal Ilmiah Pertanian ( JIPERTA), 2026)
The potential of former C-excavation mining land differs significantly from agricultural soil in terms of productivity and nutrient availability. Ecosystem restoration and soil productivity enhancement in marginal lands are necessary to improve crop productivity. This study aims to evaluate the effectiveness of biochar-coated humate (Bicomat) and Tithonia compost fertilizer on the growth and yield of bok choi (Brassica rapa L.) in two different soil types. The research was conducted from October to December 2024 The study employed a Randomized Block Design (RBD) with a non-factorial approach, consisting of three replications and eight treatments Observation of growth parameters included plant height (4 Weeks after transplanting/WAP), root length (4 WAP), number of leaves (1-4 WAP), at the time of harvest wet weight and dry weight were observed. The data that has been obtained from the observation results then will be tested using the analysis of variance (ANOVA) further test of Tuckey HSD with 5% significance. Result showed the addition of Bicomat and Tithonia Compost showed differences in plant height 4 MST, number of leaves 4 MST, fresh -dry weight of bok choi plants. The S2T2B2 (Soil 2 + 300 g Tithonia Compost + Bicomat 20 t/ha) treatments more optimal in increasing plant height 4 MST, number of leaves 4 MST, dry weight of mustard plants on post C-excavation mining land. The S1T1B2 (Soil 1 + 200 g Tithonia Compost + Bicomat 20 t/ha) treatment was optimal in increasing plant height 4 MST, number of leaves 4 MST, dry weight of mustard plants on agricultural land.